MoS2/CoS heterostructures grown on carbon cloth as free-standing anodes for high-performance sodium-ion batteries. Issue 14 (24th March 2023) - Xue, Fangfang; Fan, Feifan; Zhu, Zhicheng; Zhang, Zhigang; Gu, Yuefeng; Li, Qiuhong
Abstract : The MoS2 /CoS heterostructure on carbon cloth (MoS2 /CoS@CC) was synthesized for SIBs anode. Both experimental results and DFT calculations manifest that the MoS2 /CoS heterostructure can powerfully enhance the Na + storage performances of MoS2 /CoS@CC. Abstract : Heterostructure construction with mixed transition metal sulfides has been recognized as a promising strategy to boost the performance of sodium-ion batteries (SIBs). Herein, a carbon-decorated MoS2 /CoS heterostructure on carbon cloth (MoS2 /CoS@CC) as a free-standing anode for SIBs was synthesized via a facile growth-carbonization strategy. In the composite, the generated built-in electric field at MoS2 and CoS heterointerfaces is beneficial for elevating the electron conductivity, thus expediting the Na-ion transport rate. Moreover, different redox potentials between MoS2 and CoS can effectively mitigate the mechanical strain induced by repeated Na + de-/intercalation, thus ensuring the structural integrity. In addition, the carbon skeleton derived from the carbonization of glucose can enhance the conductivity of the electrode and maintain the structural integrity. Consequently, the resulting MoS2 /CoS@CC electrode delivers a reversible capacity of 605 mA h g −1 at 0.5 A g −1 after 100 cycles, and prominent rate performance (366 mA h g −1 at 8.0 A g −1 ). Theoretical calculations also confirm that the establishment of a MoS2 /CoS heterojunction can powerfully promote the electron conductivity, thereby enhancing the Na-ion diffusion kinetics.